The Impact of Osteoporosis and Thoracic Kyphosis on the Parameters of Quality of Life in Postmenopausal Women - Zeinab Mohammadjannataj; Sedigheh Kahrizi; Noshin Bayat (Vesnu Publications, 2020)
Introduction: Osteoporosis is caused by a loss in the bone mass and the subsequent complications decrease quality of life (QOL) of the patients. This study is performed aiming to determine the effects of osteoporosis and thoracic kyphosis on the parameters of QOL in postmenopausal women. Materials and Methods: This was a case-control study in which 53 postmenopausal women participated according to the T-score and thoracic kyphosis and were divided into four groups. Then, QOL and also different fields were compared among the groups using the 36-Item Short Form Health Survey questionnaire (SF-36). The data analysis was performed using SPSS software. Results: According to the results, the impact of osteoporosis on total scores of QOL was not significant (P = 0.783). In the areas of QOL, there was a significant difference only in the area of pain (P = 0.030). However, there was a significant difference regarding the effect of postural kyphosis on the total score of QOL (P = 0.021). In addition, in the fields of mental health problems, energy, mental feelings, and general health status, the differences were significant (P < 0.050). Conclusion: Comparing the two factors affecting QOL in postmenopausal women (osteoporosis and postural kyphosis), it was revealed that the increased thoracic kyphosis had a more remarkable role in lowering the total score of QOL. Therefore, it is necessary to correct this situation in postmenopausal women.